Digital Word of Mouth Communication Strategies in Building Customer Loyalty to the @jelione Brand - Jessycha Lionita Lubis (Journal of Communication, Sustainability, and Empowerment, 2026)
Local perfume brand @jelione utilizes Word of Mouth (WOM) communication strategies to build customer loyalty. Online perfume purchases offer limited sensory experiences, making conversations via Instagram and WhatsApp an important aspect in shaping consumer perceptions and trust before making a purchase. This study uses a descriptive qualitative approach with a focus on analyzing consumer experiences that are not only related to user experiences with physical products, but also Communication Experiences formed through digital interactions. The results show that @jelione's WOM strategy is oriented towards creating positive and authentic communication experiences, including through active responses to comments and Direct Messages (DM) by utilizing usergenerated content. This two-way communication has been proven to increase brand credibility and customer emotional attachment. This study contributes to strengthening interactive marketing communication research through the application of a symmetrical two-way communication model, emphasizing that trust, interaction quality, and communication satisfaction are key factors in shaping customer loyalty to products that cannot be directly tested by the senses.